A pan-chromatic view of clusters of galaxies and the large-scale structure - Plionis, Manolis (Springer, 2017)
Gas Dynamics in Clusters of Galaxies -- Dynamics of the Hot Intracluster Medium -- Dynamics of Galaxies and Clusters of Galaxies...